Vitamin E contents of processed meats blended with palm oils - Wan Rosli, W. I.; Babji, A.S.; Aminah, A.; Foo, S. P.; Abd Malik, O. (Wiley, 2006)
The vitamin E contents of beef burgers and chicken frankfurters blended with palm oil (PO) were determined. PO and red PO cooked beef burgers resulted in a significant (P 0.05) loss of vitamin E from 427.5 to 178.0 mg/g and from 367.0 to 271.0 mg/g, respectively, after 6 months of storage. The concentration of alpha-tocopherol (a-tocopherol) for all retorted chicken frankfurters was reduced (P 0.05) by 66.0–91.50 (16–46%) mg/g while the alpha-tocotrienol (a-tocotrienol) in all retorted chicken frankfurters significantly decreased (P 0.05) by 63.0–95.5 mg/g (28–48%) after 6 months of storage. Both a-tocopherol and a-tocotrienol decreased at a faster rate (62– 64% and 53–61% loss, respectively) and was less stable than the gammatocotrienol (12–59%) and the delta-tocotrienol (4–28%) in beef burgers. The effect of processing, cooking, frozen storage and the type of fats used could influence vitamin E stability and content in meat products.